DESIGN, MICRO-MANUFACTURING, AND CHARACTERIZATION OF A NEW FAST PARALLEL-PROCESSING FOURIER TRANSFORM INTERFEROMETER (FTIR) WITH SINGLE NON-PERIODIC PULSE CAPABILITY - SASCHA PIERRE HEUSSLER (2010)
Ph.D